Pengaruh Likuiditas, Profitabilitas dan Struktur Aktiva terhadap Struktur Modal pada perusahaan Multinasional Sektor Energi di BEI - Anggun Fitria Novianti; Astri Astri; Isma Isalahul Mustaqim; Perwito Perwito (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study examines the effect of liquidity, profitability, and asset structure on capital structure in multinational companies using panel data (30 observations) and a Fixed Effect Model (FEM) based on Chow and Hausman tests. Liquidity is measured by the Current Ratio (CR), profitability by Return On Assets (ROA), asset structure by the proportion of fixed assets, and capital structure by the Debt to Asset Ratio (DAR). The simultaneous test results indicate that CR, ROA, and asset structure jointly have a significant effect on capital structure (F-statistic = 16.33394; p = 0.000). Partially, liquidity has a negative and significant effect on capital structure, meaning higher liquidity leads to lower debt usage. Profitability and asset structure also have negative effects but are not significant. The adjusted R-squared value of 0.8088 shows that 80.88% of capital structure variation can be explained by the model variables. These findings highlight liquidity as the dominant factor in determining capital structure policy in multinational companies.